2015
DOI: 10.1097/mbp.0000000000000140
|View full text |Cite
|
Sign up to set email alerts
|

Cuff inflations do not affect night-time blood pressure

Abstract: Discomfort related to cuff inflation may bias 24 h ambulatory blood pressure (BP) measurements, especially during night-time. We accessed the impact of cuff inflations by comparing 24 h BP recorded with a cuff-less tonometric wrist device and an upper-arm oscillometric cuff device. Fifty-three participants with type 2 diabetes were assigned randomly to four 24-h BP recordings with a cuff (TM2430: visit 1 or 2, and 4) and a tonometric device (BPro: visit 1 or 2, 3, and 4). The mean 24 h systolic BP was signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Subjects reported less discomfort related to the tonometric device compared to the oscillometric device, and they preferred monitoring with the tonometric device if they had to repeat monitoring. This is in line with finding from Petersen et al [19]. In addition, they also reported that nocturnal BP and BP decline, despite patients reported nocturnal discomfort related to use of an inflatable upper arm monitor, was not influenced by this discomfort.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Subjects reported less discomfort related to the tonometric device compared to the oscillometric device, and they preferred monitoring with the tonometric device if they had to repeat monitoring. This is in line with finding from Petersen et al [19]. In addition, they also reported that nocturnal BP and BP decline, despite patients reported nocturnal discomfort related to use of an inflatable upper arm monitor, was not influenced by this discomfort.…”
Section: Discussionsupporting
confidence: 90%
“…Difference in nocturnal SBP decrease or nighttime levels between tonometric and oscillometric measurements have been reported in a study from 2015 on 53 diabetes patients by Petersen et al [ 19 ], in a study by Komori et al . [ 20 ] in young normal- and prehypertensive patients, and in the previous study of hypertensive patients by our group [ 21 ].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…This could be attributable to inconsistency of nocturnal dipping patterns [22] or direct interruption of sleep due to the operation of the ABPM device. Poor sleep quality is associated with increased BPV [23] and with increased BP [24], but it is contentious whether ABPM devices impair sleep quality enough to produce a significant increase in nocturnal pressures [25,26]. We were not able to analyse the effect of sleep quality in this study, but sleep duration did not appear to have a significant effect on night-time variability.…”
Section: Discussionmentioning
confidence: 74%